What do we mean when we talk about culture? Notes about the name of a problem - Güell, Pedro (Revista de Sociología, 2008)
Besides its importance, the concept of culture has had a difficult path through the Social Sciences. Its uses are multiple and its definitions ambiguous. This paper's general hypothesis is that the concept of culture does not pretend to be the reference of an object, but seeks to establish a perspective or a wide frame to define and face modern society as a paradox: the division between subjectivity and social order. On the one hand, this article indicates that this paradox has its origin in the crisis of the Enlightenment's promise regarding subject's autonomy and that the concept of culture was one of the privileged routes to define and face that crisis. On the other hand, it affirms that the use of the concept of culture in sociology refers to the identification of a tension between the subjective foundations of the world's meaning and the objective autonomy of the dynamics that produce order and social integration, being, at the same time, a group of mediation proposals between them. With this purpose, this paper analyzes the use and meaning of the concept present in Simmel's, Weber's and Durkheim's works. Finally, it presents the reasons that allow supposing that the use and meaning of the concept of culture in those authors can also be found in many of their successors.